Dynamic programming-based control system development for advanced electric power drive - Swapnil Ramesh Wadkar; Sudhir Madhav Patil; Maneetkumar R. Dhanvijay; Kiran Ashokrao Chaudhari; Atul Vasant Karanjkar (Institute of Advanced Engineering and Science, 2023)
An efficient method for raising the effectiveness and performance of fuel cell electric vehicles (FCEVs) is the dynamic programming controller (DPC). By using real-time data to optimize the control inputs, FCEVs can achieve higher levels of efficiency and reduce their environmental impact. The DPC algorithm works by solving an optimization problem at each time step, based on the current state of the vehicle and its environment. The optimal control inputs are then applied to the vehicle to achieve the desired performance criteria. This paper presents the study that utilized MATLAB/Simulink to design, model, and simulate DPC for a FCEV. Controlling various components of the fuel cell (FC) with the optimum power requirement is needed for increasing the performance and mileage of the FCEV. It's important to use FC energy as effectively as possible. Having supervisory control over the FCEV's energy consumption and battery charging is necessary for it to produce this output at its best. To use the hydrogen efficiently, a control strategy is designed for energy management in FCEV. The designed control strategies are implemented through simulation using Simulink in MATLAB. The results show prominent performance of dynamic programming (DP) over rule-based controllers.